Representasi Orang Baik Dalam Teks Video “Anies Baswedan’s Great Speech, Mengapa Jokowi” - Anggi Anggi Tanjung (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2015)
AbstractResearch conducted using the method of critical discourse analysis Norman Fairclough was found that Anies try to generalize the concept of good people. At the same time then blurs the meaning variants of the well itself. Emphasis and repetition of words good people who do Anies Baswedan to attach the adjective